New species and subspecies descriptions do not and should not always require a dead type specimen - Donegan, Thomas M. (Zootaxa, 2008)
Dubois & Nemésio (2007) recently considered that the present International Code for Zoological Nomenclature (“Code”) could reasonably be interpreted as requiring the deposition of dead vouchers for new species and subspecies descriptions. They considered that, to the extent that there is lack of clarity, the Code should be amended so as to require the deposition of a dead voucher. They doubted the utility of photographs and other materials for descriptions and suggested that ethical or moral concerns about the taking of dead type specimens were poorly supported. Dubois & Nemésio (2007)’s preferred interpretations of the current Code are not supported by members of the Commission. Possible reasons why the collection of a dead type specimen might not be necessary or recommended include the setting of a good example to communities in whose hands conservation action lies, government permit issues and the description of new taxa on the brink of extinction where collecting may impact populations. The Code should be liberal in relation to the nature of type specimens to enable taxonomists, who are the persons best placed to take decisions, to make appropriate judgments for particular descriptions.